Note about the first swarming in a laboratory colony of Coptotermes gestroi (Isoptera: Rhinotermitidae) - Costa-Leonardo, A. M. [UNESP]; Arab, A. [UNESP]; Hertel, H. (My University, 2005)
A laboratory rearing of Coptotermes gestroi which swarmed from the reared colony is described.
Keywords: Alates; Dispersal flight; Imagoes; Subterranean termite; Coptotermes gestroi; Isoptera; Rhinotermitidae